Internet use and subjective well-being in China - Peng Nie; Galit Nimrod; Alfonso Sousa-Poza (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2015)
Using data from the 2010 China Family Panel Studies, we analyze the association between Internet use and various measures of subjective well-being (SWB) in a sample of 16- to 60- year-old Chinese. Our analysis shows that although intensive Internet use is significantly associated with lower levels of SWB, we hardly observe any associations when the focus is on participation in specific online activities. Nevertheless, SWB depends on perceptions of Internet use; that is, the importance that different individuals ascribe to different purposes for using the Internet and how much they believe that their Internet use is displacing other activities. Our results suggest that, contrary to previous findings, differences in beneficial outcomes (the third level digital divide) do not necessarily arise from individuals' actual Internet use (the second level digital divide) but rather may result from their subjective perceptions of such usage. Our findings also point to a possible cultural factor that puts Chinese Internet users at psychological risk.
urn:nbn:de:bsz:100-opus-11047
Keywords: I10; D10; J10; Q53; 330; China; digital divides; depression; happiness; Internet use; life satisfaction